Correlação das microestruturas de amostras de dolomitas do quadrilátero ferrífero, MG com as temperaturas iniciais de hidratação das dolomas - Marcilio Dias de Carvalho (2005)
The slag agressivity during steel making in basic oxygen furnace (BOF) process has been attributed to its capacity of dissolving different refractories components, especially MgO (magnesia). Adding magnesia as dolomitic limestone, dolomitic lime has allowed the reduction of refractories attacks by corrosion, as long as raw materials presentingenough reactions rates are used. Several reviews already edited about the theme have permitted foreseeing of conditons of wearing, as well as the mettalurgical reactions wich have to be controlled increase to the life of the refractories. This document presents studies about thermal, chemical, microstructural, and others features of dolomitic limestones and lime samples, from Quadrilátero Ferrífero, Minas Gerais, Brazil. The methodology used was to apply two reactivity lime tests, with destiledwater and chloridric acyd, in order to determine initial reaction times of the samples. The main results were determining that the dolomitic limes were with high reactivities calcinated from samples with small grains (medium diameter bellow than 10 micrometers) or samples without grains, originated from mud´s limestone geological deposits or micrites. The most important results were reactiviti graphics measured fromdolomitic limes obtained from 36 samples from Quadrilátero Ferrífero, divided in three classes: High reactivity (fine grains, less than 10 micrometers or without grains-micrites) Medium reactivity (medium grains, between 10 40 micrometers) Low reactivity (large grains, above 40 micrometers)